NANDA-NIC-NOC methodology for the mental health resident nurse - Natalia Cámara Conde; Julián Carretero Román; Ángela García Pozo; Marta Menéndez Rubiera; Javier Sánchez Alfonso; Nuria Sekade Gutiérrez (Fundación para el Desarrollo de la Enfermería, 2008)
As residents of the mental health specialty, we take great care plan with methodology NANDA-NOC-NIC (NNN) in each of our rotations. Because of that there is still no consensus on how to use this methodology; we made this poster with our proposal. To do this, we propose a practical and standardized to carry out the care plans to guide future resident nurse of mental health in their care plans.Taking into account the review of various models of existing ratings of nursing at present, as well as taxonomy NNN, we carried out the development of a poster in which we show a practical example of how our proposed structure of a care plan:Evaluation: through functional patterns of M. Gordon Diagnosis: respecting the PES format: - (P) Problem: Using with the NANDA taxonomy - (E) Etiology: related factors- (S) Signs and symptoms: definitorial characteristics Planning: depending on the diagnosis set forth, the NOCs will agree. Performance indicators are also defined, specifying the current state, as well as the level to maintain /achieve and the time to be assessed. Lastly proposed interventions (NIC) and developed activities to be carried out to achieve the expected results. Implementation: implementation of interventions and activities Evaluation: we review the performance indicators, assessing the level reached in light of the current situation of the patient, and proposing corrective measures if necessary. As discussion could conclude that we used in our rotations this structure, so that we standardized "way we do." In turn, we have disseminated this structure in the National Congress of Mental Health Nursing.